BOOK REVIEW INTERNATIONAL MIXED MARRIAGE IN INDONESIA AND ASEAN - Arijati, Lita (Indonesia Law Review, 2019)
This book is focusing the commitment of marriage between two individuals who have two different nationalities or which involves two or even more legal systems results in a contact or connection between different legal systems. This contact or connection arises from a situation whereby the bride and the groom do not have the same nationality, or are not living in the same state, or do not have the nationality of the country in which they live.